Association between arsenic exposure and inflammatory cytokines and C-reaction protein: A systematic review and meta-analysis. Issue 50 (16th December 2022) - Zhang, Zheyu; Pi, Ruozheng; Luo, Jieya; Liu, Ji; Zhang, Aihua; Sun, Baofei
Abstract : Background: Previous studies have reported controversial results on levels of inflammatory cytokines in patients with arsenic exposure. This study aims to evaluate the associations between arsenic exposure and inflammatory cytokines and C-reaction protein (CRP). Methods: We searched the databases including PubMed, Embase, Web of Science, and China national knowledge infrastructure (CNKI) for studies reporting levels of cytokines and CRP in patients with arsenic exposure compared to the controls. The retrieval time was from January 2000 to September 2022. Results: 13 observational studies involving 1665 arsenic exposed and 1091 unexposed individuals were included. Among these studies, 6 from China, 4 from India, 2 from Bangladesh and 1 from Turkey. Our result showed that interleukin (IL)-6, IL-8, and IL-12 levels were significantly higher in arsenic-exposed individuals compared to the control group, IL-2 level was significantly lower, and Tumor necrosis factor- α, Interferon- γ, CRP, and IL-10 levels were not changed. After sensitivity analyses, tumor necrosis factor-α and Interferon-γ levels were significantly higher in arsenic-exposed individuals compared to the control group. High heterogeneity was detected in most studies. Conclusion: Many cytokines (such as IL-6, IL-8, and IL-12) have altered in individuals with arsenic exposure, this indicates arsenic exposure could trigger the cell-mediated inflammatory response. Regular examining immune function (such as inflammatory cytokines) in individuals with the risk of arsenic exposure is important to human health.